Search for new phenomena in events with a photon and missing transverse momentum in pp collisions at s√=8 TeV with the ATLAS detector - Onofre, A. (2015)
Results of a search for new phenomena in events with an energetic photon and large missing transverse momentum with the ATLAS experiment at the LHC are reported. Data were collected in proton--proton collisions at a center-of-mass energy of 8 TeV and correspond to an integrated luminosity of 20.3 fb−1. The observed data are well described by the expected Standard Model backgrounds. The expected (observed) upper limit on the fiducial cross section for the production of such events is 6.1 (5.3) fb at 95% confidence level. Exclusion limits are presented on models of new phenomena with large extra spatial dimensions, supersymmetric quarks, and direct pair production of dark-matter candidates.